Public preferences for redistributive policies in Israel - Yuval Elmelec (Levy Economics Institute of Bard College, 2014)
This paper contributes to the literature on inequality and welfare policy by studying public support for redistributive policies in Israel, a society with an extreme level of socioeconomic inequality. Drawing on the relevant literature and taking into consideration the distinct demographic makeup of contemporary Israeli society, the study aims to describe public support for opportunity-enhancing and outcome-based redistributive policies and to explore the extent to which individual economic and demographic characteristics are associated with policy preferences. Analysis of data from a unique topical module of the 2008 Israel Social Survey reveals that support for opportunity-based programs is strong overall, but that the Israeli public is deeply divided along ethnic lines, religious affiliation, and immigration status. While results from multinomial regression analyses provide support for the self-interest theory, the findings also underscore the significance of various demographic and social indicators as determinants of policy preferences. These findings are discussed in light of the current debates on the sources of, and possible remedies for, the growing social and economic polarization within Israeli society.
Keywords: D63; H59; 330; Israel; Public Opinion; Redistributive Policies; Social Policy Preferences